The scale of homogeneity in the Las Campanas redshift survey - Amendola, Luca; Palladino, Emilia (The astrophysical journal. Part 2, Letters, 1999)
We analyze the Las Campanas Redshift Survey using the integrated conditional density (or density of neighbors) in volume-limited subsamples up to unprecedented scales (200 Mpc h -1 ) in order to determine without ambiguity the behavior of the density field. We find that the survey is well described by a fractal up to 20-30 Mpc h -1 but flattens toward homogeneity at larger scales. Although the data are still insufficient to establish with high significance the expected homogeneous behavior, and therefore to rule out a fractal trend to larger scales, a fit with a cold dark matter-like spectrum with high normalization well represents the data.